Modification of custom tray and occlusal scheme in edentulous with abnormal relationship and compromised ridge - Franky Wielim; Ariyani Dallmer; Ricca Chairunnisa; Ismet Danial Nasution (Indonesia Prosthodontic Association, 2023)
Complete denture treatment in compromised ridges with class III jaw relationship are a challenge for prosthodontist because difficult to obtain a maximum denture bearing area in compromised ridges and to fulfil favorable functional and esthetics teeth arrangement. The purpose of this paper is to describe the modification of the custom tray, im-pression technique and teeth arrangement in edentulous case with flabby ridge, flat ridge and class III jaw relation-ship. A 58-year-old man came to Dental Hospital of Universitas Sumatera Utara with a chief complaint his loose den-ture was broken. Intraoral examination, full edentulous with flabby ridge on anterior region of maxilla, left and right maxillary tuberosity, flat ridge in maxilla and mandible with a class III jaw relationship were observed. The treatment planning included modifying custom tray and occlusal scheme. The modified custom tray of maxilla consists of dual tray with magnet retained which are made of autopolymerizing acrylic resin and thermoplastic vacuum formed. Cock-tail impression technique was used on mandible. A modified buccalized occlusion scheme to obtain good function and esthetic in class III jaw relationship. By these modification techniques, great outcome was obtained in terms of retention, stability, esthetics and functionality.